Shaping stability - Mahmoudi, Ahmed (Managing global transitions, 2025)
This paper assesses the tripartite link between a country’s financial (in) stability, its level of financial development, and economic growth. Using a panel of 21 countries over the period 2001–2020 and using the IMF Financial Market Index to proxy financial development, we find (i) that financial stability varies positively with the development of the financial system, and (ii) that the relationship between financial stability and economic growth depends critically on the level of financial development of each country. These results show that in the absence of financial development, the impact of economic growth on financial (in)stability will havedifferent effects. In addition, we performed a subsample analysis by dividing the overall sample into two subsamples based on stability levels. We find that financial development enhances stability more in the more stable subsample, while growth does so in the less stable subsample.
Keywords: economic growth; emerging and developing markets; financial (in)stability; financial development; financial market index; finančna (ne)stabilnost; finančni razvoj; gospodarska rast; indeks finančnega trga; trgi v vzponu in razvijajoči se trgi